Archibald Motley Jr. and Racial Reinvention : The Old Negro in New Negro Art - Wolfskill, Phoebe (Book collections on Project MUSE., 2017)
An essential African American artist of his era, Archibald Motley Jr. created paintings of black Chicago that aligned him with the revisionist aims of the New Negro Renaissance. Yet Motley's approach to constructing a New Negro--a dignified figure both accomplished and worthy of respect--reflected the challenges faced by African American artists working on the project of racial reinvention and uplift. Phoebe Wolfskill demonstrates how Motley's art embodied the tenuous nature of the Black Renaissance and the wide range of ideas that structured it. Focusing on key works in Motley's oeuvre, Wolfskill reveals the artist's complexity and the variety of influences that informed his work. Motley's paintings suggest that the racist, problematic image of the Old Negro was not a relic of the past but an influence that pervaded the Black Renaissance. Exploring Motley in relation to works by notable black and non-black contemporaries, Wolfskill reinterprets Motley's oeuvre as part of a broad effort to define American cultural identity through race, class, gender, religion, and regional affiliation.